An analysis on drivers of international investment decisions in South Africa - Baloyi, Livhuwani (My University, 2018)
Many developing countries are trying to make their business environment more attractive to foreign investors. They try this by relaxing rules regarding market entry and foreign ownership; improving infrastructure and making other efforts to enhance their chances of becoming a destination country for foreign direct investment (FDI). Among the characteristics of globalisation is the unrestricted capital flow and access to world market. Global FDI stocks have been on the increase and many more African countries are becoming more open to FDI, even though it still remains low. Therefore, the main objective of this study is to provide an analysis of the driving factors towards foreign direct investment in South Africa. The ARDL approach is used to investigate drivers of international investment decisions in South Africa using quarterly data from 2007Q1 to 2017Q1. The bounds cointegration method was chosen to analyse the long and the short run relationship amongst the variables of interest. In addition, the Granger Causality test was used to determine causal relationships between FDI and other variables. The study found that household income level had an effect in the stock of FDI. It also found that labour productivity increased the total output of goods and services and therefore impacted on the stock of FDI in the country. Public infrastructure investment and interest rates are also among the important factors that determine FDI inflow. Furthermore, the dummy variable has a significant negative effect and it shows that labour strikes and unrests affect FDI negatively. Although South Africa has implemented strategies to attract more FDI, recent political instability and labour disputes has left investor weary of the future of the economy therefore a refinement of some of these policies is needed if the country is to be successful in this regard. The county should also focus on developing and maintaining quality infrastructures in terms of, roads, telephones, internet access, water and electricity supply.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2018
Keywords: Drivers of international investment; Investment Decisions; Foreign Direct Investment; Cointegration; Investments, Foreign; Cointegration; International business enterprises